Enzyme characterisation and kinetic modelling of the pentose phosphate pathway in yeast - Messiha, Hanan L.; Kent, Edward; Malys, Naglis; Carroll, Kathleen M.; Swainston, Neil; Mendes, Pedro; Smallbone, Kieran (PeerJ, 2014)
We present the quantification and kinetic characterisation of the enzymes of the pentose phosphate pathway in Saccharomyces cerevisiae. The data are combined into a mathematical model that describes the dynamics of this system and allows us to predict changes in metabolite concentrations and fluxes in response to perturbations. We use the model to study the response of yeast to a glucose pulse. We then combine the model with an existing glycolysis model to study the effect of oxidative stress on carbohydrate metabolism. The combination of these two models was made possible by the standardised enzyme kinetic experiments carried out in both studies. This work demonstrates the feasibility of constructing larger network-scale models by merging smaller pathway-scale models.